Epidemiology and natural history of cancer of the uterine cervix - Fernán Zegarra P., Luis (2015)
The contrast presented by the incidence of cervical cancer disease in different countries of the world becomes more noticeable when it is offered by cities or localities within the same country and even areas of the same city.